Petrović-Type Inequalities for Harmonic h-convex Functions - Imran Abbas Baloch; Yu-Ming Chu (Journal of Function Spaces)
In the article, we establish several Petrović-type inequalities for the harmonic h-convex (concave) function if h is a submultiplicative (super-multiplicative) function, provide some new majorizaton type inequalities for harmonic convex function, and prove the superadditivity, subadditivity, linearity, and monotonicity properties for the functionals derived from the Petrović type inequalities.